The epidemiology of irritable bowel syndrome - Canavan, Caroline; West, Joe; Card, Timothy R. (Dove Press, 2014)
Irritable bowel syndrome (IBS) is a functional condition of the bowel that is diagnosed using clinical criteria. This paper discusses the nature of the diagnostic process for IBS and how this impacts epidemiological measurements. Depending on the diagnostic criteria employed, IBS affects around 11% of the population globally. Around 30% of people who experience the symptoms of IBS will consult physicians for their IBS symptoms. These people do not have significantly different abdominal symptoms to those who do not consult, but they do have greater levels of anxiety and lower quality of life. Internationally, there is a female predominance in the prevalence of IBS. There is 25% less IBS diagnosed in those over 50 years and there is no association with socioeconomic status. IBS aggregates within families and the genetic and sociological factors potentially underlying this are reviewed. Patients diagnosed with IBS are highly likely to have other functional disease and have more surgery than the general population. There is no evidence that IBS is associated with an increased mortality risk. The epidemiological evidence surrounding these aspects of the natural history is discussed.